Computer aided design (CAD) of a vertical transportation system in high-rise building: case of ivory tower, University of Ibadan, Ibadan (2020)
In compliance with the global building regulations, building with at least three floors and above must have lift. The Ivory Tower building in the University of Ibadan, Ibadan, Nigeria, for decades has been underutilized due to lack of convenient and less stressful vertical movement of the people within the building. The need therefore arise for the lift design system for the building. Analytical work involves in the design of lift system in building is often time consuming, laborious, rigorous and tedious. This work therefore aims at design and specifies lift system for the Ivory tower building using Computer Aided Design (CAD) approach. Standard Equation based on the lift system design was adopted in the study. Data were collected from the building site which includes the floor to floor distances and floor dimensions. The population in the 10-Storey Ivory tower building coupled with the 4 Storey Administrative building attached to it was determined using the Chartered Institute of Building Services Engineers (CIBSE) design guide (Peters R D Green 1995 and CIBSE 1991). Lift performance analysis for the building was then carried out using FORTRAN IV programming language. Appropriate and suitable lift and its specifications was then selected for the building. The maximum capacity, number of passengers, velocity, Round Trip Time, Handling Capacity, Interval, and number of lift cars of the selected lift system based on the quality of service are 450kg, 6 passengers, 2.0 m/s, 80.3seconds, 86 passengers, 17.54 seconds and 4 cars, respectively. The lift system therefore selected based on the required quality of services is four numbers 450kg-6passengers machine room less geared traction type. The lift shaft was successfully designed and the number of lift specified using the developed source code; hence the code can be used to design lift system for any building.